Orbital retinoblastoma: An update - Santosh G Honavar; Fairooz P Manjandavida; Vijay Anand P Reddy (Indian Journal of Ophthalmology, 2017)
Orbital extension is a major cause of death in children with retinoblastoma in the developing countries. Delayed detection and inappropriate management contribute to poor outcome. Conventional treatment including primary orbital exenteration or chemotherapy or radiotherapy alone result in mortality as high as 70%. The recent understanding on the role of sequential multimodal therapy with a combination of high-dose chemotherapy, followed by appropriate surgery, radiotherapy, and additional adjuvant chemotherapy has helped dramatically improve life salvage.